Developmental Care Practice and Documentation Variability in the Cardiac ICU. Issue 3 (March 2022) - Miller, Thomas A.; Elhoff, Justin J.; Alexander, Nneka M.; Butler, Samantha C.; Uzark, Karen C.; Glotzbach, Kristi L.; Mahle, William T.; Lisanti, Amy J.
Abstract : OBJECTIVES: Describe variability in developmental care practices, as documented in the electronic health record, for infants undergoing congenital heart surgery. DESIGN: Multicenter, retrospective, cohort study. SETTING: Six pediatric cardiac centers. PATIENTS: One hundred eighty-two infants undergoing one of three index operations: Norwood palliation, aortic arch reconstruction with ventricular septal defect closure, or arterial switch. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Core domains of developmental care encompassing pain assessment, feeding, infant holding, caregiver involvement, therapy, and psychosocial services were reviewed. Practices varied across individuals, institutions, and the hospital stay. At five of six sites, greater than 90% of individuals had physical or occupational therapy services as part of their care, but the day of first evaluation ranged from day of admission to postoperative day 28. Similar patterns were seen in feeding team and social work involvement. Consistent documentation of developmental care was dependent on the domain and site. Of the total days reviewed ( n = 1, 192), pain scores were documented in 95%. In those same days, documentation of whether or not a patient was out of the crib to be held varied by site from 11% to 93%. Type of oral feeding, breast versus bottle, was documented on the day prior to discharge 48% of the time. CONCLUSIONS: There are significant, quantifiable variations in documented developmental care practices at both the individual and site level. More reliable documentation of developmental care practices is required to associate these variables with later outcomes and investigate disparities in individualized developmental care practices.